The Anti-Inflammatory Effect of Chenopodium Murale in Comparison to Salvia Frigida on Atopic Eczema - Hassan, Zahraa Y.; Hassan, Tuka Y.; Kanany , Ahmed Y. (Journal of the Faculty of Medicine Baghdad, 2024)
Background: Atopic dermatitis (AD) is a prevalent chronic inflammatory skin condition with a familial tendency. It affects approximately 10%-20% of children and 1%-3% of adults worldwide. Chenopodium murale is clinically proven for treating many medical conditions, such as AD, due to its easy application and efficacy. Salvia plant has an anti-inflammatory effect on AD cases treated with phenolic compounds. Objective: To determine the anti-inflammatory effect of the phytosterol fraction of Chenopodium murale (CM) in comparison to Salvia frigida (SF). Methods: This study was conducted from December 2020 to June 2021 in the Department of Pharmacology, College of Medicine, Al Nahrain University. Fifty mice were included in the study, subdivided equally into five subgroups [control, induction, Tacrolimus-1%, Phytosterol-3%, and Phenolic-5%]. Biological and histological parameters were measured, and their means were compared using the independent t-test, and the one-way ANOVA was used to estimate the mean of differences. Results: The Tacrolimus-1% group showed a significant decrease in white blood cells, Ig-E, and inflammation means than other groups; a significant decrease in mean epidermal thickness than the Phytosterol-3% groups; and a significant decrease in IL-13 and erosion than the Phenolic-5% groups. The phytosterol-3% group showed a significant decrease in the mean parakeratosis, erosion, and observational severity (OS) score than other groups. The phenolic-5% group showed a significant decrease in the mean epidermal thickness than other groups and a significant decrease in OS score than the Tacrolimus-1% groups. Conclusion: The topical applications of the phytosterol fraction of Chenopodium murale or the phenolic compound of Salvia frigida were effective and promising in treating atopic dermatitis. While the phenolic compound of Salvia frigida is effective, it is somewhat less than that of the phytosterol fraction of Chenopodium murale.